Bioaccessibility and decomposition of cylindrospermopsin in vegetables matrices after the application of an in vitro digestion model. (October 2018) - Maisanaba, Sara; Guzmán-Guillén, Remedios; Valderrama, Rocío; Meca, Giuseppe; Font, Guillermina; Jos, Ángeles; Cameán, Ana M.
Abstract: Research on the human exposure to Cylindrospermopsin (CYN) via consumption of contaminated food is of great interest for risk assessment purposes. The aim of this work is to evaluate for the first time the CYN bioaccessibility in contaminated vegetables (uncooked lettuce and spinach, and boiled spinach) after an in vitro digestion model, including the salivar, gastric and duodenal phases and, colonic fermentation under lactic acid bacteria. The results obtained showed that the digestion processes are able to diminish CYN levels, mainly in the colonic phase, especially in combination with the boiling treatment, decreasing CYN levels in a significant way. Moreover, the potential decomposition products in a pure CYN solution and in CYN-contaminated vegetables were evaluated using UHPLC-MS/MS Orbitrap. Under the conditions assayed, only two diastereoisomers of the same fragment with m/z 292.09617 have been detected in all the analysed samples, with the exception of digested vegetables. Therefore, in terms of risk assessment, the digestion seems to play an important role in reducing the final bioaccesibility of CYN, and the consumption of cooked vegetables (spinach) would be safer in comparison to raw vegetables. Highlights: Bioaccessibility of CYN from contaminated vegetables was studied for the first time. CYN degradation has been determined after the in vitro digestion process. The colonic phase induced the most relevant decrease in CYN bioaccessibility. Decomposition products of CYN were studied in each digestive phase of vegetables.